2018
DOI: 10.1016/j.tjem.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of EFAST training for final year medical students in emergency medicine clerkship

Abstract: BackgroundExtended Focused Assessment Sonography for Trauma (EFAST) is an important bedside tool for the management of multiple trauma patients. We aimed to evaluate the assessment of our EFAST education in the Emergency Medicine Clerkship (EMC) for final year medical students and the correlations of EFAST marks with other practical skill stations and the final multiple choice question (MCQ) exam marks.MethodsFifty-four final year medical students were trained on performing EFAST on human models during their 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Less time was needed to train on the EFAST than on the RUSH protocol, with training for one hour on EFAST effectively improving both performance and interpretation [19]. We recently reported that hands-on performance was acceptable in 88% of medical students after five hours of training, including one hour of didactic training, two hours of practical training with an instructor, and two hours of free practice [10]. The current study found that only three hours of instructor-led EFAST training was sufficient to increase knowledge significantly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Less time was needed to train on the EFAST than on the RUSH protocol, with training for one hour on EFAST effectively improving both performance and interpretation [19]. We recently reported that hands-on performance was acceptable in 88% of medical students after five hours of training, including one hour of didactic training, two hours of practical training with an instructor, and two hours of free practice [10]. The current study found that only three hours of instructor-led EFAST training was sufficient to increase knowledge significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Point-of-care ultrasound (POCUS) is regarded as important [1][2][3][4], with increasing numbers of medical schools integrating ultrasound training into their undergraduate curricula [5][6][7]. Ultrasound training, once only taught in residency programs or sporadically to medical students, is now included in the teaching of undergraduate students [7][8][9][10]. However, despite the consensus that ultrasound training should be part of undergraduate training, no agreements have been reached on the length of time required for training or on its content and delivery methods [5][6][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, implementing POCUS training in medical programs including medical schools is spreading [ 72 ]. We are actually advocates of POCUS training for all our undergraduate medical students because we think it will become the stethoscope of the future [ 73 ].…”
Section: Pocus Trainingmentioning
confidence: 99%